Exposure to a glyphosate-based herbicide induces avoidance behavior and impairs coelomocyte viability in Eisenia andrei earthworms - Gelati de Batista, Diovana; Furlanetto Pinheiro, Juliana; Sulzbacher Ourique, Isadora; Barz Basso, Bethina; Todendi de Bragas, Maria Eduarda; Machado Sulzbacher, Lucas; Brendler Goettems Fiorin, Pauline; Gomes Heck, Thiago (Scientific Letters, 2024)
Background: Glyphosate-based herbicides (GBH) are the most widely used agrochemicals [1]. Earthworms are key soil organisms used as bioindicators and alternative experimental models for studying the immune system [2,3]. Objective: We tested whether agronomic dosages of GBH induce avoidance behavior and alter the immunological profile of earthworms Eisenia andrei. Methods: Adult earthworms (0.318 ± 0.007 g) were divided into four groups and exposed for 48h: Control group (native soil), GBH1.5, GBH3, and GBH6 groups (native soil with GBH at concentrations equivalent to 1.5, 3.0, and 6.0 L/ha, respectively). Under these conditions, we applied the Avoidance Behavior Test (% of animals that escape from contaminated areas) and Acute Toxicity Test. We used glyphosate (Roundup®, Original DI, Monsanto, 44.5% w/v active ingredient) or water (control) in each experimental unit (n=6; 6 animals/experimental unit, 6 replicates each, in a box with 600g of soil, 95% of dystrophic red latosol:5% organic matter). The coelomocytes were collected by a non-invasive method [4]. Results: The highest concentration (GBH6) induced avoidance behavior in earthworms (% avoidance = GBH6 = 83.3±18.2, p=0.01) without modification in the immune profile. Furthermore, there was a reduction in cell viability of the coelomocytes obtained from the GBH6 (p=0.001) and also GBH3 (p=0.01) groups, when the animals had no option to avoid the contaminated area (CTRL: 75.7±18.9%; GBH1.5: 63.7±22%; GBH3: 56.7±29.6%; and GBH6: 56.0±21.4%). Conclusion: The presence of GBH in the soil at a typical agronomic dose (3.0 L/ha) or higher (6.0 L/ha) threatens the immune defense of earthworms and may lead to the loss of the ecological function of soil.